On self-serving strategic beliefs - Nadja R. Ging-Jehli; Florian H. Schneider; Roberto A. Weber (University of Zurich, Department of Economics, 2019)
We experimentally study settings where an individual may have an incentive to adopt negative beliefs about another's intentions in order to justify egoistic behavior. Our first study uses a game in which a player can take money from an opponent in order to prevent the opponent from subsequently causing harm. We hypothesize that players will justify taking by engaging in "strategic cynicism," convincing themselves of the opponent's ill intentions. We elicit incentivized beliefs both from players with such an incentive and from neutral third parties with no incentive to bias their beliefs. We find no difference between the two sets of beliefs, suggesting that people do not negatively bias their beliefs about a strategic opponent even when they have an incentive to do so. This result contrasts with Di Tella, et al. (2015), who argue that they provide evidence of strategic cynicism. We reconcile the discrepancy by using Di Tella, et al.'s, data, a simple model of strategic belief manipulation and a novel experiment in which we replicate Di Tella, et al.'s, experiment and also elicit the beliefs of neutral third parties. Across three experimental datasets, the results provide no evidence of negatively biased beliefs about others' intentions. However, Di Tella, et al.'s, results and our novel data indicate that those with a greater incentive to view others' intentions negatively exhibit relatively less positive beliefs than those without such incentives.
Keywords: C72; D83; C92; 330; motivated beliefs; strategic cynicism; bias; experiment